FAO hallgatói mobilitások makrogazdasági mutatókkal való összefüggései Afrikában - Janik, Henrietta (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
The internationalization and internationalization of higher education is one of the most actual topics related to education today. The number of foreign students in major higher education institutions is increasing, and international collaborations in the field of education and research are becoming more frequent. However, despite the fact that the topic is so tangible in proximity, we still know a small fragment about the process of internationalization of higher education, the factors that support and hinder the phenomenon. The theoretical significance of the present study is the analysis of the revealed literature and statistical data, while the practical significance is the comparative study of the research carried out in the international context depending on the number of FAO scholarship students coming to Hungary from African countries. Examining the territorial location of the sending countries within Africa, the question arises as to why these countries send students to developed countries, in this case Hungary. Is there a correlation between certain macroeconomic indicators and the mobility tendencies or territorial orientation of students who have received an FAO scholarship?